Opportunities for investment under the CARIFORUM-EU EPA\n (The Unit BridgetownBB, 2011)
Outlines the relevant sections of the EPA which relates to the applicable arrangements for the reciprocal liberalisation of market access for investment and investors.
Keywords: PARTNERSHIP